System of management indicators for multidisciplinary educational projects - Flavia Eizerik; Ângela de Moura Ferreira Danilevicz; Istefani Carísio de Paula (Arizona State University, 2020)
This paper aims to propose a system of indicators for managing Multidisciplinary School Projects (MultiSP) as a support for decision making in schools wishing to implement this type of educational project. To this end, a survey was conducted with 51 private elementary and high schools in Brazil to identify best practices regarding MultiSPs. The elements that made up this survey were obtained considering interviews with stakeholders involved in MultiSPs and tools to support the multicriteria decision-making process, such as the Heuristic Minimization of Interdependence. Based on the survey results it was possible to map the Brazilian scenario and propose a Project Management Indicator System (KPI-MultiSP) as a tool for monitoring and improvement of MultiSPs. This system is the main contribution of this article and is formed by eight constructs and three indicators associated with each. It can serve as a starting point for schools, as its structure allows the customization of indicators. The constructs that make up the KPI-MultiSP, entitled Project Objectives, are: (i) expansion of student knowledge; (ii) student autonomy; (iii) social life; (iv) practical experimentation of the content; (v) interdisciplinarity; (vi) student protagonism; (vii) variation of school daily life; and (viii) Iron Triangle.